Creating television : conversations with the people behind 50 years of American TV - Kubey, Robert William, 1952- (LEA's communication series., 2004)
Creating Television brings television and its creators to life, presenting fascinating in-depth interviews with the creators of American TV. Having interviewed more than 100 television professionals over the course of his 15 years of research, Professor Robert Kubey presents here the 40 conversations that provide the most illuminating insights about the industry and the people working in it. These interviews bring television's creators to life, revealing their backgrounds, work, and thoughts about the audience and the television programs they create. Each interview tells a compelling ta.